Predictors of Improvement in Physical Function in Older Adults in an Evidence-Based Physical Activity Program (EnhanceFitness). Issue 4 (October 2019) - Fishleder, Sarah; Petrescu-Prahova, Miruna; Harris, Jeffrey R.; Leroux, Brian; Bennett, Kimberly; Helfrich, Christian D.; Kohn, Marlana; Hannon, Peggy
Abstract : Background and Purpose: Declines in strength, flexibility, and balance in older adults can lead to injuries and loss of independence and are particularly common in those of greater age and in worse health. EnhanceFitness (EF) is a nationally disseminated, evidence-based group exercise program for older adults that has been shown to improve function through cardiovascular, strength, flexibility, and balance exercises. This article examines changes in, and predictors of, participant physical function from baseline through 2 program cycles of EF as measured by 3 physical function tests: arm curls, chair stands, and 8-foot up-and-go. Methods: We analyzed data on participants who attended at least 2 consecutive 16-week program cycles between January 2005 and June 2016. We ran 3 random-effects linear regression models, 1 for each physical function test, and accounted for missing data and clustering by class site. Independent variables included attendance, demographics, and health status. Results and Discussion: A total of 7483 participants completed baseline and 2 sets of follow-up physical function tests. For all 3 physical function tests, participants showed some degree of improved physical function at each follow-up, and greater program attendance predicted clinically significant improvements. Some participants had less improvement: females, those less active at baseline, older than 75 years, not married or partnered, or in fair or poor health, those who had experienced at least 1 fall, and those with a disability. Conclusion: EnhanceFitness program providers may need to implement additional measures to support the participants who could benefit most from EF, such as targeting messaging, coordinating with referring providers to emphasize attendance and general activity in specific participants, and offering additional support to groups who show less improvement during classes. The evidence presented here may inform clinical decision making for older adult patients and increase health care provider confidence in EF and similar exercise programs, thereby providing a mechanism to maintain and continue functional gains made in clinical or rehabilitation settings.